Tectono-stratigraphic evolution of the northeastern sector of the Ñirihuau basin, North Patagonian Andes, Argentina: Insights from sedimentology and geochronology data of the Ñirihuau Formation. (November 2021) - Santonja, Camila; Bechis, Florencia; Suriano, Julieta; Falco, Juan I.; Encinas, Alfonso; Olaizola, Ezequiel R.; Valencia, Victor A.; Litvak, Vanesa D.; Ramos, Victor A.
Abstract: An approximately 3500 m thick stratigraphic section was detailed surveyed in order to study the tectono-sedimentary evolution of the Ñirihuau Formation along the Arroyo Las Bayas, in the northern sector of the Ñirihuau basin, North Patagonian Andes. A total amount of 29 lithofacies were recognized and used to define facies, grouped into six facies associations (FA) that reflect different paleoenvironments: FA1 (Gray to brownish conglomerates), FA2 (Conglomerates and sandstones), FA3 (Tabular mudstones), FA4 (Brownish sandstones and conglomerates with large scale foresets), FA5 (White tuffaceous sandstones) and FA6 (Sandstones and conglomerates with mudstones). The lower section of the unit was interpreted as deposited in a medium to distal alluvial fan or an axial fluvial system developed in the most distal zone of an alluvial fan (FA1 and FA2). The middle section of the unit is characterized by a Gilbert-type delta developed between two lacustrine sequences (FA3 and FA4). In the upper section of the unit, higher energy deposits corresponding to fluvial systems are registered (FA5 and FA6). Deposits from synchronic volcanic events are recorded along the stratigraphic section. Also, a provenance analysis was carried out by using sedimentary petrography and U–Pb zircon geochronology data. The main identified sediment source corresponds to the contemporaneous Miocene volcanic arc. A secondary detrital provenance from older Cenozoic volcanic rocks of the El Maitén Volcanic Belt was also identified, as well as minor contributions from pre-Cenozoic igneous and metamorphic units. U–Pb geochronological data constrain deposition of the middle and upper sections of the Ñirihuau Formation in the Arroyo Las Bayas section to the middle to late Miocene, between 15 and 11.4 Ma (Langhian to Tortonian). Also, a possible middle Miocene age was discussed for the lower section. An integrated tectono-stratigraphic model was finally proposed, with contrasting extensional and synorogenic tectonic stages registered in the lower and upper sections of the Ñirihuau Formation, respectively. Highlights: One of the best exposed stratigraphic sections of the Ñirihuau Fm. was studied. Alluvial, lacustrine, deltaic and fluvial environments were recognized. An initial extensional stage was interpreted for the lower section of the unit. Synorogenic conditions were interpreted for the upper section deposition. New U–Pb data constrain the middle and upper sections to middle and late Miocene.